PENGARUH KUALITAS PELAYANAN PETUGAS PERPUSTAKAAN TERHADAP TINGKAT KEPUASAN SISWA DI SMK KRISTEN PENABUR PURWOREJO (STIE Rajawali Purworejo, 2018)
The purpose of this study is to determine the level of student satisfaction of the services of librarians and the relationship of service quality of library staff and student satisfaction in the library. the method of analysis in this study using the valid ity test, reliability test, simple correlation, simple linear regression coefficient of determination and t test. The results of this study can be seen that there is a positive and significant influence between the quality of service librarians to student satisfaction in SMK Kristen Penabur Purworejo is Y = 13,576 + 0.679X. This is indicated by the coefficient value of 0.679. This means, if the value of service quality variables increased by one point, then the satisfaction of students will increase seber sar 0.679. In the determination coefficient test sebersar 0.450 or 45% the number shows student satisfaction that occurs and is explained by using service quality variables so that from 100%-45% so that 55% get contributions from other factors. With the criteria level α 0.05 with the number of samples of 21 students then obtained ttable of 2.080 with table level significance, α = 0.05 with a confidence level of 95% with ttable of 2.080 while the calculation based on table 4:29 which is done using t count variable service quality (X) of 3.944. Thus the value of tcount is greater than ttable (3.944> 2.080) or significant value (0.001 <0.05). So that Ha there is a positive and significant influence between the quality of service librarians to student satisfac tion in SMK Kristen Penabur Purworejo and Ho rejected